2010
DOI: 10.1186/1471-2407-10-227
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of DNA methylation in colorectal cancer reveals subgroups with distinct clinicopathological and molecular features

Abstract: BackgroundMost previous studies of the CpG island methylator phenotype (CIMP) in colorectal cancer (CRC) have been conducted on a relatively small numbers of CpG sites. In the present study we performed comprehensive DNA methylation profiling of CRC with the aim of characterizing CIMP subgroups.MethodsDNA methylation at 1,505 CpG sites in 807 cancer-related genes was evaluated using the Illumina GoldenGate® methylation array in 28 normal colonic mucosa and 91 consecutive CRC samples. Methylation data was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 45 publications
2
82
0
3
Order By: Relevance
“…Microsatellite instability (MSI), as identified by BAT25 and BAT26 instability (not the full Bethesda panel), was not detected in any of the adenomas, and all had wild-type v-raf murine sarcoma viral oncogene homolog B1 (BRAF), suggesting that the CpG island methylator phenotype (CIMP) was unlikely in these adenomas (19)(20)(21). No significant difference in global genomic DNA methylation level, as measured by pyrosequencing of CpGs within the long, interspersed nuclear element 1 (LINE-1) elements, was seen between the normal and adenomatous epithelium of each patient ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite instability (MSI), as identified by BAT25 and BAT26 instability (not the full Bethesda panel), was not detected in any of the adenomas, and all had wild-type v-raf murine sarcoma viral oncogene homolog B1 (BRAF), suggesting that the CpG island methylator phenotype (CIMP) was unlikely in these adenomas (19)(20)(21). No significant difference in global genomic DNA methylation level, as measured by pyrosequencing of CpGs within the long, interspersed nuclear element 1 (LINE-1) elements, was seen between the normal and adenomatous epithelium of each patient ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23] It has been argued that CpG island methylation phenotype-positive tumors constitute a distinct subtype of colorectal cancer, and have been variously associated with different features such as BRAF mutation, KRAS mutation, favorable prognosis and adverse outcome. [24][25][26][27][28][29][30]42 These differences are likely related to different criteria used for defining CpG island methylation phenotype-positive status, as well as the number and type of markers used. The role of methylation in signet ring cell carcinoma has not been systematically explored.…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, studies have shown that CpG island methylation phenotype-positive phenotype is associated with aggressive behavior. [26][27][28][29][30] BRAF is a downstream gene in the KRAS pathway. BRAF V600E mutation occurs in 34-80% of cancers with high level of microsatellite instability and 5-15% of microsatellite-stable cancers.…”
mentioning
confidence: 99%
“…It has been shown that genomic mutations are associated with a high frequency of cancer-specific hypermethylation of particular loci, and these may be associated with distinct DNA methylation subgroups [20][21][22]. Aberrant DNA methylation has been investigated in several types of leukemia in order to gain further insight into cytogenetic subtypes [23][24][25].…”
Section: Dna Extraction and Methylation Detectionmentioning
confidence: 99%